2015
DOI: 10.3892/mmr.2015.4309
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic variants in vitamin D signaling pathway genes and the risk of endometriosis-associated infertility

Abstract: Abstract. It has recently been reported that vitamin D blood plasma levels are associated with reduced risk of endometriosis. The present study aimed to investigate whether the vitamin D binding protein (GC), vitamin D receptor (VDR), and retinoid X receptor (RXR) gene variants may be genetic risk factors for endometriosis-associated infertility. The subjects consisted of 154 women with endometriosis-associated infertility and 347 controls. Using polymerase chain reaction restriction fragment length polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
(50 reference statements)
2
15
0
1
Order By: Relevance
“…The study conducted by Vilarino and colleagues did not find any difference in the frequency of several VDR polymorphisms (SNPs) studied by restriction fragment length polymorphisms among 132 women with endometriosis-related infertility, 62 women with idiopathic infertility, and 133 controls [42]. Similar results were reported by Szczepańska and colleagues (2015), as they did not demonstrate differences in genotype and allele frequencies of several VDR SNPs between 154 women with endometriosis-associated infertility and 347 controls [43]. …”
Section: Vitamin D and Endometriosissupporting
confidence: 53%
“…The study conducted by Vilarino and colleagues did not find any difference in the frequency of several VDR polymorphisms (SNPs) studied by restriction fragment length polymorphisms among 132 women with endometriosis-related infertility, 62 women with idiopathic infertility, and 133 controls [42]. Similar results were reported by Szczepańska and colleagues (2015), as they did not demonstrate differences in genotype and allele frequencies of several VDR SNPs between 154 women with endometriosis-associated infertility and 347 controls [43]. …”
Section: Vitamin D and Endometriosissupporting
confidence: 53%
“…Recently, it has been suggested that CYP17 , VDR , MUC17 , COX-2 , WNT4 , E-cadherin , CYP19 , CYP17 , TYK2 , NFKB1 , and MUC2 gene variants also contributed to endometriosis-related infertility [17, 4755]. …”
Section: Discussionmentioning
confidence: 99%
“…In the same study, total 25(OH)D concentrations did not significantly differ between the two groups; however, free and bioavailable vitamin D concentrations were higher among the infertile women. The genotype distribution of GC rs1155563 and rs2298849 SNPs was compared between 154 women with endometriosis-associated infertility and 347 controls; still, no statistically significant differences were detected ( 61 ).…”
Section: Vdbp As a Marker Of A Healthy Ongoing Pregnancy: Clinical Immentioning
confidence: 99%